EXPLORING TEACHERS' KNOWLEDGE, UNDERSTANDING AND REWARD PRACTICES: A MOTIVATIONAL ORIENTATION PERSPECTIVE IN MATHEMATICS LEARNING - Tampa, Alimuddin; Zaki, Ahmad; Alimuddin, Fauziyyah; Azizah Aksa, Nurul (IAIN Ambon, 2025)
The persistent gap between teachers' conceptual knowledge and practical implementation remains a critical challenge in mathematics education. This study investigates how intrinsic versus extrinsic motivational orientations influence teachers' knowledge, understanding, and reward implementation practices in mathematics instruction. Employing an exploratory qualitative case study design, the research examined 14 junior high school mathematics teachers in South Sulawesi, Indonesia, systematically classified by motivational orientation. Data collection encompassed motivational orientation assessments, conceptual knowledge evaluations, case-based understanding tasks, and structured classroom observations. Thematic cross-case analysis was conducted using NVivo 12 software. Findings reveal progressive differentiation patterns: while conceptual knowledge differences remained relatively modest, disparities amplified significantly across understanding and classroom practice dimensions. Intrinsically motivated teachers demonstrated reflective, contextualized, and process-oriented reward strategies, whereas extrinsically motivated teachers exhibited procedural, standardized, and outcome-focused approaches. These results advance theoretical understanding of motivational orientation as a critical moderating variable in knowledge-to-practice transformation processes, offering substantial implications for targeted professional development interventions addressing motivational dimensions in mathematics education.